Overexpression of long non-coding RNA TUG1 predicts poor prognosis and promotes cancer cell proliferation and migration in high-grade muscle-invasive bladder cancer - Iliev, Robert; Kleinova, Renata; Juracek, Jaroslav; Dolezel, Jan; Ozanova, Zuzana; Fedorko, Michal; Pacik, Dalibor; Svoboda, Marek; Stanik, Michal; Slaby, Ondrej (Tumor biology, 2016)
Long non-coding RNA TUG1 is involved in the development and progression of a variety of tumors. Little is known about TUG1 function in high-grade muscle-invasive bladder cancer (MIBC). The aims of our study were to determine expression levels of long non-coding RNA TUG1 in tumor tissue, to evaluate its relationship with clinico-pathological features of high-grade MIBC, and to describe its function in MIBC cells in vitro. TUG1 expression levels were determined in paired tumor and adjacent non-tumor bladder tissues of 47 patients with high-grade MIBC using real-time PCR. Cell line T-24 and siRNA silencing were used to study the TUG1 function in vitro. We observed significantly increased levels of TUG1 in tumor tissue in comparison to adjacent non-tumor bladder tissue (P < 0.0001). TUG1 levels were significantly increased in metastatic tumors (P = 0.0147) and were associated with shorter overall survival of MIBC patients (P = 0.0241). TUG1 silencing in vitro led to 34 % decrease in cancer cell proliferation (P = 0.0004) and 23 % reduction in migration capacity of cancer cells (P < 0.0001). We did not observe any significant effects of TUG1 silencing on cell cycle distribution and number of apoptotic cells. Our study confirmed overexpression of TUG1 in MIBC tumor tissue and described its association with worse overall survival in high-grade MIBC patients. Together with in vitro observations, these data suggest an oncogenic role of TUG1 and its potential usage as biomarker or therapeutic target in MIBC.
Keywords: Tumor Cells, Cultured; regulace genové exprese u nádorů; nádorové biomarkery; kvantitativní polymerázová řetězová reakce; Cell Movement; Prognosis; Real-Time Polymerase Chain Reaction; invazivní růst nádoru; Biomarkers, Tumor; Neoplasm Invasiveness; Reverse Transcriptase Polymerase Chain Reaction; RNA dlouhá nekódující; Cell Proliferation; Humans; staging nádorů; malá interferující RNA; pohyb buněk; nádory močového měchýře; Cell Cycle; Muscle Neoplasms; Neoplasm Staging; messenger RNA; RNA, Long Noncoding; prognóza; apoptóza; proliferace buněk; polymerázová řetězová reakce s reverzní transkripcí; nádorové buňky kultivované; nádory svalů; Disease Progression; Urinary Bladder Neoplasms; Gene Expression Regulation, Neoplastic; RNA, Small Interfering; ženské pohlaví; RNA, Messenger; lidé; buněčný cyklus; progrese nemoci; Apoptosis; Female